Pemanfaatan Alga Coklat Sargassum sp pada Pembuatan Kemasan Air Mineral yang Dapat Dikonsumsi - Rizqia, Nurfatia; Rahayu, Susanti; Thifalia Sahda3, Nabila; Sukreni, Tulus (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Bottled mineral water has become a daily necessity for Indonesians for its practicality. The raw material used in mineral water packaging is plastic because the price is cheaper, and the characteristics of it are strong and lightweight when compared to other polymers. However, the plastic waste produced is difficult to be decomposed by microorganisms in the soil, causing environmental pollution. There have been many researches on the production of environmentally friendly plastic packaging. One of the raw materials used is alginate because it contains ester compounds which are the required for making biodegradable plastics. The alginate compound contained in seaweed is a polysaccharide obtained from the extraction of brown seaweed such as Sargassum sp which is found in Indonesian waters. Gel formation can be done by diffusion with the spherification method. This method is the simplest technique, where the gel is formed by diffusion of calcium ions into the alginate solution. The results showed that sodium alginate derived from seaweed can be used as a raw material in the production of mineral water packaging that can be consumed by using the spherification techniques. The packaging product which is shaped like a bubble is safe for consumption and is biodegradable